Wages in African public administrations: Where do we stand? - Guillaume Delautre; Giulia de Lazzari; Gustavo Rinaldi (International Labour Organization (ILO), 2025)
By playing a key role in the provision of critical services, such as health, education or security, governments are crucial for the good functioning of societies and social justice. Governments have a dual role to play as employers and as the actor responsible for the good management of the economy. This document aims to provide a synthetic picture of the situation of the wages of African public administration employees, based on the latest data available, and to discuss some of the current challenges for public-sector wage policies in Africa.
Keywords: 330